Changes in growth, sugar and starch contents in groundnut (Arachis hypogaea L.) plants under nickel toxicity - Vijayaragavan3, D.Ezhilvannan1*, P.S. Sharavanan2; M. (Current Botany, 2011)
Treatment of groundnut (Arachis hypogaea L.) Ã‚Â with different concentrations of nickel decreased the growth parameters and biochemical contents. The experiment was conducted at Botanical Garden, Department of Botany, Annamalai University, Tamil Nadu. In the pot culture experiment, groundnut plants were analysed on two different sampling (viz., 15th and 30th) days, in soil amended with various levels of nickel (viz, 10, 30, and 50 mg kg-1). The inner surfaces of pots were lined with a polythene sheet. Each pot containing 3kg of air dried soil. Six seeds were sown in each pot. All pots were watered to field capacity daily. Plants were thinned to a maximum of three per pots, after a week of germination. Nickel at all levels (10,30 and 50mg kg-1) tested, decreased the growth parameters such as, root and shoot length, fresh weight of root and shoot and biochemical constituents such as, sugar and starch contents of groundnut plants compared to untreated plants.